Guest Editorial - Jannicke Baalsrud Hauge (Serious Games Society, 2017)
This special issue presents five papers bringing new insights into the field of accessibility and serious games. This is a special issue from the workshops and the doctorial consortium from the 15th International Conference on Entertainment Computing 2016 hosted by professor Helmut Hlavacs at the University in Vienna, Austria (https://icec2016.cs.univie.ac.at/index.php?item=home).